Alcohol, drug and related health and wellbeing issues among young people completing an online screen. (April 2017) - Barker, S Fiona; Manning, Victoria; Best, David W; Savic, Michael; Lubman, Dan I
Objective: Despite high levels of alcohol use, drug use and risky behaviors, rates of help-seeking amongst young people are typically low. This study explored the profile of young people (under the age of 25 years) completing an online screen, assessing substance use problem severity and wellbeing in comparison with adults completing the same screen, so as to inform development of better targeted approaches for this in-need population. Methods: Between 2012 and 2014, an online alcohol and drug screen was promoted across Australia on a national online counseling service. The screen assessed severity of substance use, mental health and wellbeing. Results: A total of 2939 screens were completed between December 2012 and May 2014, with 18% completed by young people. Young people reported a high severity of substance use problems (44% reported likely drug dependence) and reported significantly poorer mental health and wellbeing than adults completing the screen. This suggests that there is a population of young people in need of support who could be initially engaged through online screening. Conclusions: Online screening should be a key component of engagement strategies for adolescent and early adult help-seeking.